A Case Report of Sustained Cytokine Release Syndrome Due to Glofitamab and Literature Review - Yang J; Shen Q; Ke X; Liu W; Yang P (Clinical Pharmacology: Advances and Applications)
Jingyi Yang,1– 3,* Qian Shen,1,4,* Xiaoyan Ke,5 Wei Liu,1,3 Ping Yang5 1Department of Pharmacy, Peking University Third Hospital, Beijing, 100191, People’s Republic of China; 2Department of Pharmacy Administration and Clinical Pharmacy School of Pharmaceutical Sciences, Peking University, Beijing, 100191, People’s Republic of China; 3Institute for Drug Evaluation, Peking University Health Science Center, Beijing, 100191, People’s Republic of China; 4The second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, 710004, People’s Republic of China; 5Department of Hematology, Peking University Third Hospital, Beijing, 100191, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Liu, Department of Pharmacy, Peking University Third Hospital, Beijing, 100191, People’s Republic of China, Email liuwei0023@bjmu.edu.cn Ping Yang, Department of Hematology, Peking University Third Hospital, Beijing, 100191, People’s Republic of China, Tel +8610-13488693764, Email yangping198302@163.comAbstract: Glofitamab is a novel bispecific antibody targeting CD20×CD3, capable of simultaneously targeting CD20 and CD3 to activate T cells and release cytotoxic proteins that kill cancer cells. Cytokine release syndrome (CRS) is one of the most common adverse events observed in clinical trials of glofitamab. In most cases, CRS is mild, transient, and manageable with appropriate treatment. This paper reports a case of persistent CRS in a patient with mantle cell lymphoma following glofitamab treatment and reviews the relevant literature for reference.Keywords: glofitamab, cytokine release syndrome, cytokines, interleukin-6